A Systematic Screening of ADHD-Susceptible Variants From 25 Chinese Parents–Offspring Trios - Li, Qianqian; Meng, Yingying; Wang, Jingyang; Xie, Yuhang; Li, Tian; Sun, Wei (Frontiers in Genetics, 2022)
Attention-deficit/hyperactivity disorder (ADHD) is one of the most prevalent and heritable childhood behavioral disorders. Although a number of ADHD susceptible regions had been identified, details about the variations of genes and their related patterns involved in ADHD are still lacking. In this study, we collected 25 Chinese parents-offspring trios, each of which consisted of a child diagnosed as ADHD and their unaffected parents, and analyzed the variations from whole genome sequencing data. SNVs in reported ADHD susceptible regions and on the genes whose functions were related to dopamine were screened, and we identified a set of variants with functional annotations and specifically detected in ADHD children, including most SNVs in gene coding region that might impair protein functions and a few SNVs in promoter or 3’ untranslated region (3’-UTR) that might affect the regulation of relative gene expression in transcriptional or post-transcriptional level. All the information may further contribute to the understanding, prediction, prevention and treatment of ADHD in clinical.